Sutureless Aortic Valve Replacement - Makhdoum, Ahmad (My University, 2019)
Aortic Stenosis (AS) is the most common valvular heart disease. Aortic valve replacement (AVR) is the only acceptable treatment for AS. Several replacement methods are available to treat AS including conventional surgical aortic valve replacement (SAVR), transcatheter aortic valve replacement (TAVR), and Sutureless aortic valve replacement (SuAVR). SAVR showed excellent long-term results. However, it is an invasive procedure and is denied in substantial number of patients. TAVR showed excellent results and outcomes when compared to SAVR. However, it is associated with increased rate of paravalvular leaks that may impact long term outcomes. SuAVR has developed to overcome the drawbacks of SAVR and TAVR. SuAVR is associated with favorable short and midterm outcomes when compared to SAVR and TAVR. In this thesis, we summarize the safety, the evidence and the perceptions of using SuAVR in Canada. In Chapter1, we evaluated the use of SuAVR Perceval bioprosthesis in retrospective single center study of 415 patients with AS. SuAVR showed excellent immediate post-operative and hemodynamics outcomes. In chapter 2, we sought to establish perceptions and patterns to SuAVR use among Canadian cardiac surgeons. Sixty-Six Canadian cardiac Surgeons responded to the survey. Surgeons reported influential factors, barriers to use SuAVR, and their interest in a trial comparing SuAVR versus TAVR. Surgeons were likely to use SuAVR in high risk patients with hostile aortic root, small aortic annulus and in patients undergoing concomitant procedures whereas cost was the main limiting factor to use SuAVR in Canada. Majority of surgeons reported their interest in participating in a trial comparing SuAVR with TAVR. In chapter 3, we systematically reviewed and meta-analyzed the international evidence of using SuAVR versus SAVR and TAVR. SuAVR showed favorable or comparable results to SAVR and TAVR. However, long term and randomized data are needed to confirm these results.
Keywords: Aorta; SuAVR; Sutureless; Aortic Valve Replacement